Perbaikan Level Tegangan dan Reduksi Rugi-Rugi Sistem Transmisi Sulbagsel Berbasis Ant Colony Optimization - Kitta, Ikhlas (Politeknik Negeri Ujung Pandang, 2019)
Abstract—The Ant Colony Optimization (ACO) method is used to determine the location and optimal amount of bank capacitors in the South Sulawesi electric power system (Sulbagsel). The purpose of employing ACO is to determine the ability of ACO as one method for optimization to improve voltage levels and reduce power losses in the electric power system. There are 5 scenarios carried out in this study, scenario 4 and scenario 5 are scenarios for applying the ACO method, the results of these two scenarios are the increase in voltage on the bus and the reduction of power losses in the Sulbagsel system.